Serat Centhini: Sebuah Kompleksitas Kesusastraan Jawa yang Mumpuni - Anies Widiyarti (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2013)
‘Serat Centhini’, also known as ‘Suluk Tambanglaras’ or ‘Suluk Tambangraras-Amongraga’, is one of the greatest works in the New Javanese Literature, written in form of ‘tembang’ (songs). The work contains various kinds of Javanese knowledge and culture. Using literary sociological approach, this article discusses about ‘Serat Centhini’. As one of literary canons, ‘Serat Centhini’ is said as a smart, innovative and very complete work. It is found that ‘Serat Centhini’ successfully integrates three perpectives in literary sociology, such as a) seeing a literary work as a social document, b) seeing a literary work as the reflection of the author’s social situation, and c) seeing a literary work as the manifestation of a certain historical event and cultural situation. Finally, the fact that this work has been one of the greatest works deals with Pakubuwono V’s initial intention to make ‘Serat Centhini’ be the encyclopaedia of the Javanese culture.